Development of QuizWhizzer Media for Islamic Religious Education Evaluation at SMP NU Palangka Raya - Safitri, Natasya Audia; Jumrodah, Jumrodah; Zulkarnain, Ali Iskandar (Jayapangus Press, 2025)
QuizWhizzer is a digital game-based evaluation medium that offers interactive and engaging learning experiences. This study aims to develop QuizWhizzer as an evaluation tool for Islamic Religious Education (PAI) at SMP NU Palangka Raya. The research employed a Research and Development (R&D) method using the ADDIE model and a descriptive qualitative approach. The study was conducted from April 10 to June 10, 2025, involving Grade VIII-2 students. The instruments used included media expert validation questionnaires, evaluation questions, and teacher and student response questionnaires. The validation results indicated that the media is highly feasible for use, with scores of 98% from media experts, 97.5% from item experts after revisions, and response instrument validation scores of ≥81%. Teacher and student responses were also positive, at 91.67% and 70% respectively. The test items demonstrated high validity, a reliability coefficient of 0.86, varied difficulty levels, good discrimination power, and effective distractors. This study concludes that QuizWhizzer is suitable for use as an interactive digital evaluation medium, particularly for the topics of buying and selling, usury (riba), and debt. The novelty of this research lies in the use of a gamification platform for PAI learning evaluation at the junior high school level, which remains uncommon, especially through the use of the QuizWhizzer digital game board that enables interactive and game-based assessment.